2018
DOI: 10.1038/s41598-018-32897-y
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of olfactory- versus visual-signal encounter by searching bumblebees

Abstract: While the phrase ‘foraging bumblebee’ brings to mind a bumbling bee flying flower to flower in a sunny meadow, foraging is a complicated series of behaviors such as: locating a floral patch; selecting a flower-type; learning handling skills for pollen and nectar extraction; determining when to move-on from a patch; learning within-patch paths (traplining); and learning efficient hive-to-patch routes (spatial navigation). Thus the term ‘forager’ encompasses multiple distinct behaviors that rely on different sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 87 publications
0
15
0
Order By: Relevance
“…Unfortunately, agrochemicals are not the sole source of odor pollutants that pollinators contend with-previous work has shown that air pollutants, such as diesel exhaust and ozone, react with floral odorants [11][12][13][14][15]. This reduces the distance that floral odors travel, which could have impacts on signal encounter by searching foragers [8,12]. In addition, the reaction of floral odorants with air pollutants changes the blend structure-in some cases pushing a learned odor far enough that honeybees no longer respond normally [13][14][15].…”
Section: Understanding Generalization and Discrimination Behavior Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, agrochemicals are not the sole source of odor pollutants that pollinators contend with-previous work has shown that air pollutants, such as diesel exhaust and ozone, react with floral odorants [11][12][13][14][15]. This reduces the distance that floral odors travel, which could have impacts on signal encounter by searching foragers [8,12]. In addition, the reaction of floral odorants with air pollutants changes the blend structure-in some cases pushing a learned odor far enough that honeybees no longer respond normally [13][14][15].…”
Section: Understanding Generalization and Discrimination Behavior Of mentioning
confidence: 99%
“…Flowers provide multiple sensory advertisements to pollinators; such as shape, color, and scent [5][6][7]. Recent computational work indicates that odor is consistently available to searching bumblebees [8] and labbased experiments indicate that bumblebees are capable of using odor information alone to locate floral resources [9,10]. Floral-scent is likely an important sensory cue for bumblebee foragers; unfortunately anthropogenic activity has modified their olfactory landscape in urban, suburban and agricultural ecosystems [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Bumblebees are an important model for this work because they tightly regulate both their colony (Schultze-Motel, 1991;Jones and Oldroyd, 2006;Gardner et al, 2007) and brood temperatures (Vogt, 1986;Weidenmüller et al, 2002). The proper development and function of sensory systems in bumblebees is essential for their pollination activities as they rely heavily on visual, olfactory, gustatory and mechanosensory information to navigate between flower patches and their colony (Dyer and Chittka, 2004;Orbán and Plowright, 2014;Wilmsen et al, 2017;Sprayberry, 2018) and to optimise their foraging (Spaethe et al, 2001;Chittka et al, 2003;Kulahci et al, 2008). Furthermore, bumblebees are already experiencing range shrinkage and population declines in both Europe (Kerr et al, 2015) and North America (Cameron et al, 2011;Kerr et al, 2015) as a result of a warming climate.…”
Section: Introductionmentioning
confidence: 99%
“…Plants attract pollinators to their flowers using several signals, including flower display, size, shape, color, and odor [18][19][20][21][22][23]. Each signal is relevant for pollinators foraging for floral rewards, pollen, and nectar [24], as pollinators often exhibit innate preferences [25].…”
Section: Introductionmentioning
confidence: 99%